2017
DOI: 10.1002/ps.4738
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase coordinates larval–pupal tanning and immunity in oriental fruit fly (Bactrocera dorsalis)

Abstract: These results suggest that BdTH might play a critical role in larval-pupal tanning and immunity of B. dorsalis, and could be used as a potential novel target for pest control. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 44 publications
7
41
0
Order By: Relevance
“…In Agrotis ipsilon , most of the CRISPR/Cas9‐mediated AiTh knockout embryos can develop but cannot hatch, while the other successfully hatched embryos died within the first day . Similarly, injection dsRNA against Th or feeding TH inhibitor lead to a severe obstacle to larval‐pupal metamorphosis and adult eclosion in Tribolium castaneum , Anopheles sinensis and several fly species, followed by death in most cases . From these findings, we conclude that Th is an important survival gene in holometabolous insects.…”
Section: Introductionmentioning
confidence: 80%
“…In Agrotis ipsilon , most of the CRISPR/Cas9‐mediated AiTh knockout embryos can develop but cannot hatch, while the other successfully hatched embryos died within the first day . Similarly, injection dsRNA against Th or feeding TH inhibitor lead to a severe obstacle to larval‐pupal metamorphosis and adult eclosion in Tribolium castaneum , Anopheles sinensis and several fly species, followed by death in most cases . From these findings, we conclude that Th is an important survival gene in holometabolous insects.…”
Section: Introductionmentioning
confidence: 80%
“…In the process of melanin formation, both PO and TH catalyze tyrosine hydroxylation to generate the melanin precursor dopa. Dopa is then transformed into dopamine with the catalyzation of DDC, and finally melanin is formed . Entomovirus indirectly affects the melanization of insect herbivores by reducing the melanization enzyme activity in insect hemolymph.…”
Section: Introductionmentioning
confidence: 99%
“…Dopa is then transformed into dopamine with the catalyzation of DDC, and finally melanin is formed. [19][20][21][22] Entomovirus indirectly affects the melanization of insect herbivores by reducing the melanization enzyme activity in insect hemolymph. For instance, inhibition of melanization by NPV infection in cotton bollworm caterpillars was due to reduced levels of PO activity in the infected host hemolymph.…”
Section: Introductionmentioning
confidence: 99%
“…Some melanin biosynthesis pathway genes, including tyrosine hydroxylase ( TH ), phenylalanine hydroxylase ( PAH ) and Lac2 have been associated with the melanotic encapsulation immune responses triggered by microorganism infections in certain insect species ( Infanger et al, 2004 ; Qiao et al, 2016 ; Du et al, 2017 ; Chen et al, 2018 ). A recent study demonstrated that Lac2 silencing in A. sinensis significantly reduced the resistance to the exogenous bacteria Serratia marcescens and Bacillus bombyseptie , implying that Lac2 participates in melanotic immune responses ( Du et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%